Renewable energy sources impact on economic growth: international practices - Viktoriia Bozhanova; Oleksandra Kononova; Carolina Dodu-Savca; Larisa Dodu-Gugea; Olena Chernysheva (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
Energy is an indispensable source of power for economic development. Mainstream research has concluded that energy can be divided into two types: renewable and non-renewable. Research analyzing the impact of non-renewable energy on economic development is very comprehensive. Researchers dispute the association between expanding the usage of renewable energy sources and stimulating the economy. They investigated the connection between economic growth and energy use in developing countries. The paper assesses the impact of the energy transition to renewable energy sources driving the economic growth of countries. It has been established that positive transformations in economies can be seen both developed and emerging economies. It has been proved that economic growth, once the national energy becomes autonomous (examples of Iceland, Uruguay), ensures the economy protection from external fluctuations in energy prices and guarantees electricity generation at prices lower than those set for the energy produced from fossil sources. The paper shows that freedom from additional financial burden for businesses is a critical precondition for the stable development of the economy during the energy transition period. It is indicated in the paper that if the state cannot carry out such a transition on its own, there are good reasons to engage large businesses and other participants in this process on favourable contractual terms. It has been found that such actions will promote increased investments in the development of renewable power generation in the country. The paper studies the main opportunities for economic growth resulting from the energy transition, including price advantages for power generation (prices for electricity produced using alternative sources are cheaper than those for electricity produced from fossil sources), driving the entrepreneurial activity, as well as the possibility of exporting energy produced from renewable source. The scientific novelty of our research is in the development of the question of the energy impact transition on the economic growth of countries with different financial, economic and energy potential, through the establishment of specific characteristics of this process, which can contribute to the modeling of its implementation at the level of other states, including Ukraine.